Evolution of Faculty of Information Management (FIM): Transformation of FIM 1968 to 1980) / Nursyazwani Arzunaidi - Arzunaidi, Nursyazwani (Faculty of Information Management, 2015)
There have been so many improvements made during the development of Faculty of Information Management as time passed. The existance of Faculty of Information Management was been introduced since 1968.Eventhough they are a different era, different name, but they have the same objective which is to produce a professional people in Library Science.